The "Ways of Midrash" in the biblical commentaries of Isaac Abarbanel - Lawee, Eric (Hebrew Union College annual / Jewish Institute of Religion, 1996)
The prolific and versatile theologian and exegete, Isaac Abarbanel (1437—1508), produced a rich corpus of biblical commentaries which, among other things, is remarkable for the creative and variegated interaction that it evinces between Abarbanel and midrash. This article explores characteristic motivations, concerns, and objectives that governed Abarbanel's incorporation of diverse sorts of midrashic dicta into his commentaries, highlighting especially the critical importance of the interplay of exegetical and theological considerations in his assessment of individual (and at times whole classes of) midrashim. The beginning of the article briefly locates Abarbanel's encounter with the rabbinic hermeneutic in two salient Iberian contexts. The first, historical, pertains to an evolution in medieval Hispano-Jewish tastes in biblical interpretation. There was a strong sense among Spanish Jews — stimulated partially, it would seem, by Jewish awareness and appreciation of Christian achievements in this sphere — that Scripture's multilayered profundity needed urgently to be probed. The second context concerns an immanent development within the discipline of Hebrew scriptural exegesis as practiced by Iberian-born commentators. Reservations about or hostility to inclusion of midrashim in works of biblical commentary like that often displayed by earlier Andalusian interpreters receded and midrashic dicta were, for a variety of reasons, increasingly accorded a significant place and warm reception in works by commentators such as Nahmanides, Bahya ben Asher, Abarbanel, Isaac Arama, and others.